К ВОПРОСУ О ПРАВОВОЙ ПРИРОДЕ ХИМИЧЕСКОЙ БЕЗОПАСНОСТИ РЕСПУБЛИКИ КАЗАХСТАН (Journal of actual problems of jurisprudence, 2019)
In this article the author gives concept of chemical safety and opens its maintenance. Also the parity of ecological safety andchemical safety as conditions of maintenance of a sustainable development of Republic Kazakhstan is defined